(untitled) (Research, Society and Development, 2021)
Education has sought to adapt its role to the current demands of society, among them, the promotion of equality and learning opportunities. In order to start an understanding of this process, this work sought to describe and analyze the conceptions and practices of some teachers, from the municipality of Aracaju-SE, who teach Sciences, about the process of inclusion of students with intellectual disabilities (ID) in classrooms regular education. The survey was conducted in six schools in Aracaju, from the application of 16 questionnaires to teachers of Elementary School I and II. The data were interpreted using the Bardin Content Analysis method (2016). The results revealed that the intellectual is the most expressive of the deficiencies in the municipality, however, the teachers consulted do not consider themselves qualified to attend DI students in regular classes, given that this unpreparedness is due, according to them, both from deficiencies in initial training. as for continuing education, which requires changes in the current conjuncture of education and the training curriculum of science teachers. For Inclusive Education to be potentiated, it is suggested that teachers be trained to use methodologies focused on the student, so that all students can develop their potential based on the construction of scientific thinking, based on curiosity and the action of interaction with the medium to which they are inserted.